Effect of β-hydroxy-β-methylbutyrate (HMB) on the Muscle Strength in the Elderly Population: A Meta-Analysis - Lin, Ziru; Zhao, Anqi; He, Jiguo (Frontiers in Nutrition, 2022)
Abstract Objective: This meta-analysis aims to evaluate the effect of the emerging nutritional ingredient β-hydroxy-β-methylbutyrate (HMB) on the muscle strength of elderly people. Methods: Computer systems-based search and sorting of relevant documents published before December 2020 in the China Journal Full-text Database (CNKI), Wan Fang Database (Wan Fang), VIP Chinese Science and Technology Journal Database (VIP), PubMed, Web of Science, and EMbase Database was done. Two researchers independently screened the literature based on the inclusion and exclusion criteria and performed data extraction and quality evaluation. Rev Man 5.X software was used for systematic review and meta-analysis. Results: A total of 9 randomized controlled trials (RCT) studies were included in the study, which comprised 896 subjects. The overall impact on muscle strength-related indicators (SMD = 0.41; 95% CI: 0.28, 0.54); p<0.00001) was statistically significant. Conclusion: Supplementation of HMB as well as preparations containing HMB ingredients aids in increasing muscle strength in the elderly population.